Plutonium reactive transport in fractured granite: Multi-species experiments and simulations. (1st October 2022) - Zhang, Xiaoying; Wang, Zheng; Reimus, Paul; Ma, Funing; Soltanian, Mohamad Reza; Xing, Baoshan; Zang, Jianzheng; Wang, Yu; Dai, Zhenxue
Highlights: The transport behaviors of Pu colloids, Pu(IV) and Pu(V-VI) were investigated. The mobility is decreased from Pu colloid, Pu(V-VI) to Pu(IV). Different models can describe the sorption of Pu in an unequivocally way. Sorption rate constants of Pu tend to decrease with increasing time scales. Abstract: Plutonium (Pu) in the subsurface environment can transport in different oxidation states as an aqueous solute or as colloidal particles. The transport behavior of Pu is affected by the relative abundances of these species and can be difficult to predict when they simultaneously exist. This study investigates the concurrent transport of Pu intrinsic colloids, Pu(IV)(aq) and Pu(V-VI)(aq) through a combination of controlled experiments and semi-analytical dual-porosity transport modeling. Pu transport experiments were conducted in a fractured granite at high and low flow rates to elucidate sorption processes and their scaling behavior. In the experiments, Pu(IV)(aq) was the least mobile of the Pu species, Pu(V-VI)(aq) had intermediate mobility, and the colloidal Pu, which consisted mainly of precipitated and/or hydrolyzed Pu(IV), was the most mobile. The semi-analytical modeling revealed that the sorption of each Pu species was rate-limited, as the sorption could not be described by assuming local equilibrium in the experiments. The model was able to describe the sorption of the different Pu species that occurring either on fracture surfaces, in the pores of the rock matrix, or simultaneously in both locations. While equally good fits to the data could be achieved using any of these assumptions, a fracture-dominated process was considered to be the most plausible because it provided the most reasonable estimates of sorption rate constants. Importantly, a key result of this work is that the sorption rate constant of all Pu species tends to decrease with increasing time scales, which implies that Pu will tend to be more mobile at longer time scales than observations at shorter time scales suggest. This result has important implications for predicting the environmental impacts of Pu in the safety assessments of geologic repositories for radioactive waste disposal, and we explore potential mechanistic bases for upscaling the sorption rate constants to time and distance scales that cannot be practically evaluated in experiments. Graphical abstract: Image, graphical abstract